Impactos socioambientais, planejamento urbano e habitação social: Uma análise do Programa Minha Casa Minha Vida na cidade de Uberaba-MG - Rodrigues, Pamela de Almeida (2023)
This paper discusses housing developments in vulnerable socio-environmental areas of the city of Uberaba, Minas Gerais. The Minha Casa Minha Vida program has contributed significantly to the production of social housing in the city, with more than eight thousand units contracted by FAR companies. However, most of these units are located in areas with inadequate urban infrastructure, and often in areas that are detrimental to the comfort of residents and/or pose possible socio-environmental risks. Our hypothesis is that the poor location of these developments is due to a system that prioritizes developers over local organizations. Therefore, our goal is to investigate the socio-environmental damage caused by the construction of these developments. To achieve this goal, we conducted bibliographical and documentary research to understand how Brazilian housing policies have operated since 2009 and the housing development program (PMCMV) in Uberaba, to understand who are the actors involved in this process, who built the subdivisions and where they are located. In addition, we evaluated the use of urban planning policies in the housing development process. By conducting a temporal comparison, we noticed that the city's ZEISs were not aligned with the goals of the Estatuto da Cidade. Based on our analysis, three urban development projects were studied in depth: Alfredo Freire IV Stages 1 and 2 and Parque dos Girassóis IV. This study identified significant socio environmental risks and vulnerabilities related to their respective locations. To conduct our study, we used McHarg's Suitability Analysis methodology, developed in 1969. Additionally, we applied the "Urban Insertion Assessment Tool for Developments in the Minha Casa Minha Vida Program", co-developed by LabCidade and ITDP Brazil. Through the use of different collection techniques, including documentary and bibliographical sources, direct observation of the sites and maps, and Geographic Information Systems analysis, we found that the settlements all had inadequate performance in all of the methods applied. The sites lack adequate access to public transportation, urban infrastructure, commerce, and services. They are also located in regions with potential environmental vulnerabilities. Although there are recommendations and methodologies for the development of these allotments, which consider the social-environmental aspects, in practice they were not observed in Uberaba.